Socialization of new student admissions for an increase in the gross participation rate of universities in Bandar Lampung City: en - - Karomani; - Mualimin; Ryzal Perdana (Jurnal Sumbangsih, 2021)
Socialization is a process, in which a new member of society learns the norms and values of which he or she is a member. This socialization is done as a form of effort from universities to be able to provide information about the admission of new students. This aims that information about this can be conveyed properly in accordance with the Mandate of the Ministry of Education and Technology which expects that there is an increase in the Gross Participation Rate (APK) of Higher Education in Indonesia, especially in bandar Lampung City. The low Gross Participation Rate (APK) of Higher Education in Indonesia in 2018 showed a figure of 33.37%. This figure shows the lag when compared to some other communities in ASEAN. Seeing this, Lampung University as one of the universities also organizes socialization of new student admissions every year. The new student admission system is carried out through the test path determined by the Ministry of Education and Technology. In addition, Lampung University also held student admissions through the achievement path as a form of appreciation of Indonesian students who have ability both in the academic and non-academic fields. Socialization of new student admissions of Lampung University to increase the Gross Participation Rate of Universities in Bandar Lampung City is generally done through online and direct socialization on a limited basis while still complying with health protocols. This socialization activity is also continued with evaluation and monitoring so that the activities run well and the desired essence and objectives can be achieved.